(untitled) (Myagdi Guru, 2024)
Mergers, acquisitions and takeovers, consolidation have been a part of the business world for so many years. The purpose of this study is to examine the impact that mergers and acquisitions have had on the employees’ satisfaction of the commercial banks in Nepal. This study aims to examine the association between merger and acquisition and the employee satisfaction of commercial banks. A descriptive research design and a casual comparative research design were used for this research. Three commercial banks were selected by using purposive sampling method. The study employed a quantitative approach using a sample of employees of commercial banks in Pokhara. The study is based on primary data where a survey was conducted to identify the view of employees. Various tools used for data analysis are mean, standard deviation, correlation, and regression through a comprehensive analysis of pre- and post-merger data. The result revealed that working condition is key factor in employee satisfaction in merged commercial banks. Job security, pay scale, and organizational culture, while important do not significantly impact overall employee satisfaction. This finding suggests that employees highlight a positive work environment over financial incentives. Yet, an unexplored research area involves how post-merger changes in organizational culture impact employee engagement, and future research direction for financial institutions like insurance companies in s in Nepali context.